2017
DOI: 10.1186/s40657-016-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of climate factors in geographic variation in body mass and wing length in a passerine bird

Abstract: Background: Geographic variation in body size is assumed to reflect adaptation to local environmental conditions. Although Bergmann's rule is usually sufficient to explain such variation in homeotherms, some exceptions have been documented. The relationship between altitude, latitude and body size, has been well documented for some vertebrate taxa during the past decades. However, relatively little information is available on the effects of climate variables on body size in birds. Methods:We collected the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Previous studies have demonstrated that the body mass or body condition of Eurasian Tree Sparrows vary with life-history stage (Li et al 2008(Li et al , 2011(Li et al , 2012Zheng et al 2014) and living environment (Zhang et al 2011;Sun et al 2016Sun et al , 2017. Furthermore, male sparrows during the early breeding stage had significantly greater Hct values compared to those from the early wintering stage, whereas there were no significant differences in SCM between the two life-history stages (Zhao et al 2017).…”
Section: Open Accessmentioning
confidence: 61%
“…Previous studies have demonstrated that the body mass or body condition of Eurasian Tree Sparrows vary with life-history stage (Li et al 2008(Li et al , 2011(Li et al , 2012Zheng et al 2014) and living environment (Zhang et al 2011;Sun et al 2016Sun et al , 2017. Furthermore, male sparrows during the early breeding stage had significantly greater Hct values compared to those from the early wintering stage, whereas there were no significant differences in SCM between the two life-history stages (Zhao et al 2017).…”
Section: Open Accessmentioning
confidence: 61%
“…There is no agreement about whether Bergmann's pattern is general or valid (Blackburn et al 1999;Meiri and Dayan 2003;Watt et al 2010;Teplitsky and Millien 2014). Empirical studies have found the predicted pattern at both the intraspecific and interspecific levels (Meiri 2011;Salewski and Watt 2017) in numerous mammals (Ashton et al 2000;Rodriguez et al 2008) and birds (Olson et al 2009;Sun et al 2017). At the same time, animals that do not conform to Bergmann's rule have also been reported (Yom-Tov et al 2002;Freeman 2017;Sargis et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Great body mass and muscle weight in highland are concordance with Bergmann's rule [15,16]. Avian pectoralis is used to support the high metabolic costs through aerobic metabolism for flight or thermogenesis [4].…”
Section: Pectoralis Variations To Highland Survivalmentioning
confidence: 81%